Things hoped for - Clements, Andrew, 1949-2019 (Scholastic Inc., 2006)
Seventeen-year-old Gwen, who has been living with her grandfather in Manhattan while she attends music school, joins up with another music student to solve the mystery when her grandfather suddenly goes missing.